Reputation Management and Customer Experience Strategies in Preventing Fraud in Wedding Organizer Service Providers and Its Implications for Increasing Sales (Case Study on Twin Wedding Organizers) - Radha Mazly Nasution; Evawany Yunita Aritonang; Meilita Tryana Sembiring (Majapahit Journal of Islamic Finance and Management, 2026)
The crisis of public trust due to the rampant cases of fraud (Ponzi schemes and defaults) in the Wedding Organizer (WO) industry has created serious Customer Trust Issues, demanding an integrity-based strategic response. This study aims to analyze the role of Reputation Management Strategy (X1), measured through Transparency and Integrity, and Customer Experience (X2), realized through Employee Competence and Professionalism, as a function of fraud prevention, and examine its implications on Sales Increase (Y1)Case study was conducted on Twin Wedding Organizers in Medan City, involving 150 client respondents and using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) for data analysis. The results of the study show that Strategies (X1) and (X2) have proven to be significant in overcoming Customer Trust Issues (M1), confirming that eliminating Opportunity (financial transparency) and reducing Pressure (team competence) is the key to restoring trust. Success (M1) then serves as a crucial mediator that increases Positive Customer Experience (M2), which ultimately correlates significantly with Increased Sales (Y1). These findings resulted in a 3-Pillar Trust Management Strategy Model that recommends Trust-Based Governance (use of Escrow Account), Competence-Led CX, and Reputation Amplification, making it a practical guide for WO professionals in Medan to make integrity a competitive advantage.